INFORMATION ABOUT THE QARA-TATARS IN MUSLIM SOURCES OF THE 13th CENTURY - Timokhin D.M. (Золотоордынское обозрение)
Research objectives: This article is devoted to the analysis of references by Muslim historians to the ethnonym “Qara-Tatars”. Most often, researchers turned to this problem in relation to the events of the late 14th – early 15th centuries, as V.V. Bartold already did, mentioning the “Qara-Tatars” whom Timur resettled from the borders of Asia Minor to Transoxiana. However, we would like to draw attention to the fact that Muslim historians of the 13th century also reported about the “Qara-Tatars” and these descriptions have not yet been the object of special study in Russian research. In this article, we will not only try to analyze these data, but also correlate them with the stories about the nomadic Turkic tribes of the Dasht-i Qipchaq whose names also contain the color marker “qara”/”black” in even earlier Muslim texts. Such a study should be useful not only to specialists in the history of the nomadic Turkic tribes of the Dasht-i Qipchaq, but also to those whose interests are related to the analysis of the evolution of Muslim historiography of the 11th – 13th centuries, as well as to researchers of the semantics of color in the names of Turkic tribal associations.Research materials: The main materials on which this article is based are both Muslim historical and geographical works written in the 13th century, as well as a number of earlier texts to which later authors referred or from which they borrowed information. In addition, we will take into account the sources of the Armenian historical tradition which contain information about the “Qara-Tatars” and the Mongol conquests of the first half of the 13th century.Research results and novelty: In this article, among the Muslim writings of the 13th century, the mention of the “Qara-Tatars” in the list of Turkic tribes was noted, cited by Fakhr-e Modabber in his essay “Shajara-ye ansab-e mobarakshah-i”, as well as a lengthy description of this tribal association in the work, “Sharh nahj al-balaga”, by Ibn Abu al-Hadid al-Mada’ini. The first example highlights the fact that pre-Mongol authors were already familiar with this tribal association, and the second example clearly demonstrates the influence of much earlier Muslim historians and geographers on the authors of the 13th century.